ANALISIS RENCANA PELAKSANAAN PEMBELAJARAN TEMATIK GURU KELAS IV MIS BAWARI PONTIANAK - Agus Susilariani; Siti Halidjah; Hery Kresnadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
Abstract The problem in this research is "What is the thematic lesson plan (RPP) prepared by the grade IV teacher of MIS Bawari Pontianak?". The form of research used is descriptive with the case study method. Sources of data in this study were teachers of class IV MIS Bawari Pontianak with indicators in the form of observation sheets for the completeness of the components and the accuracy of the content of the lesson plans. The results of the study, the whole lesson plan from the 1st, 2nd, and 3rd lessons did not include very important things, namely learning indicators where this indicator is a benchmark in the formulation of goals. The learning steps are not in sync with the written cooperative learning model because it does not display cooperative learning steps. For assessment, there is no enrichment / remedy program. In the lesson plan assessment, this lesson plan does not attach questions or tests carried out in the 1st lesson, but as a whole contains a knowledge assessment grid, however, in this lesson plan write down an attitude assessment indicator rubric. Keywords : Analysis, Cooperative Learning, Thematic